2003
DOI: 10.1089/088282403322017893
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal IgG and IgA Responses to Human Papillomavirus Type 16 Capsid Proteins in HPV16-Infected Women without Visible Pathology

Abstract: Human papillomavirus type 16 (HPV16) may infect the cervical epithelium without producing pathological changes for a long time. To investigate if mucosal antibodies are induced in HPV16-infected women without visible pathology, cervical mucus from HPV16-infected patients with and without evident pathology, along with mucus from uninfected women were analyzed for the presence of mucosal IgG and secretory IgA (sIgA) antibodies to HPV16 capsid proteins by ELISA. sIgA and IgG antibodies were found in a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
11
0
2
Order By: Relevance
“…The primary analysis of a large Phase III study in women 15 to 25 years of age confirmed the high efficacy against CIN2 or greater (CIN2+) associated with HPV types 16 and 18, which was up to 98% in an HPV naive cohort (HPV seronegative and DNA negative for oncogenic types) which approximates young adolescents before sexual debut [144]. The end of study analysis revealed that overall vaccine efficacy on CIN2+, irrespective of HPV type, was 64 Currently no studies are available where the efficacy of the AS04-adjuvanted HPV-16/18 vaccine and the HPV-6-11-16-18 vaccine are compared. Whether the differences observed in the immune profile of the two vaccines have an influence on the magnitude of protection in the long-term still remains to be determined.…”
Section: Efficacymentioning
confidence: 84%
See 1 more Smart Citation
“…The primary analysis of a large Phase III study in women 15 to 25 years of age confirmed the high efficacy against CIN2 or greater (CIN2+) associated with HPV types 16 and 18, which was up to 98% in an HPV naive cohort (HPV seronegative and DNA negative for oncogenic types) which approximates young adolescents before sexual debut [144]. The end of study analysis revealed that overall vaccine efficacy on CIN2+, irrespective of HPV type, was 64 Currently no studies are available where the efficacy of the AS04-adjuvanted HPV-16/18 vaccine and the HPV-6-11-16-18 vaccine are compared. Whether the differences observed in the immune profile of the two vaccines have an influence on the magnitude of protection in the long-term still remains to be determined.…”
Section: Efficacymentioning
confidence: 84%
“…A cell-mediated immune response of effector T lymphocytes directed against the early E2 and E6 HPV proteins occurs first, as reflected by the infiltration of specific helper and cytotoxic T lymphocytes, macrophages, and the local production of proinflammatory cytokines [4,60,61]. Approximately 8 months after infection, low levels of neutralizing antibodies to the major capsid protein L1 may appear in the serum of infected individuals, and specific IgG and secretory IgA are found locally in the cervical mucosa, but at very low levels [62][63][64]. …”
mentioning
confidence: 99%
“…Mucosal antibodies recognizing HPV16 capsids have been detected in a proportion of HPV16-infected patients (Wang et al, 1996;Bontkes et al, 1999;Rocha-Zavaleta et al, 2003;Sasagawa et al, 2003;Bierl et al, 2005). It has been suggested that mucosal antibodies may protect against HPV16 infection and cervical disease (Bierl et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…HPV16 capsids have been demonstrated to be highly immunogenic. Indeed, although minimal amounts of virions are exposed to the immune surveillance cells (O'Brien & Campo, 2002), mucosal antibodies against HPV16 capsids have been detected in infected women (Wang et al, 1996;Bontkes et al, 1999;Rocha-Zavaleta et al, 2003;Sasagawa et al, 2003;Bierl et al, 2005). In the context of HPV infections, mucosal immune responses may play an important role in preventing subsequent viral infections and spreading.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, all previous reports studied the systemic response to survivin mediated by IgG-class antibodies. In our case, we decided to investigate the mucosal response because cervical cancer derives from the cervical mucosal epithelium, which is known to play an important role in the generation of local immune responses to diverse challenges, including those associated with the development of cervical cancer [26,27]. To the best of our knowledge, this is the first time that a mucosal IgA-mediated response against autologous survivin is reported in cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%